A novel ultrasonic tip for removal of filling material in flattened/oval-shaped root canals: a microCT study - Melissa Esther RIVERA-PEÑA; Marco Antônio Húngaro DUARTE; Murilo Priori ALCALDE; Flaviana Bombarda DE ANDRADE; Rodrigo Ricci VIVAN (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The aim of this study was to evaluate the influence of a novel ultrasonic tip as an auxiliary method for removing filling material from flattened/oval-shaped canals. The null hypothesis tested was that this method does not influence removing the filling material in flattened/oval-shaped canals. Forty-five mandibular incisors were selected and randomly divided into three experimental groups (n = 15) according to different protocols for removing root canal filling material. Group R: Reciproc R25/.08, Group RC: Reciproc R25/.08 + Clearsonic tip, and Group CR: Clearsonic tip + Reciproc R25/.08. The teeth were scanned pre and post-operatively by means of a micro-computed tomography system. Data were analyzed using non-parametric Kruskal-Wallis and Dunn tests (p < 0.05). The percentage of residual root canal filling material between the experimental groups was examined. Statistically significant differences between the experimental groups were found in the root canal. Group R had the highest percentage of residual root canal filling material when compared with Groups RC and CR. The lowest percentage of residual root canal filling material was observed in Group CR. In the apical third of the root canal, statistically significant differences were found between the different protocols. The use of the ClearSonic tip followed by the Reciproc 25/.08 file to remove filling material resulted in the lowest percentage of residuals in the whole root canal and in the apical third.